IF IT’S ITCHY, ITS SCABIES... NOT ALWAYS - ., Safiullah; Qureshi, Muhammad Salman Haider; Ali, Saima; Khan, Imtiaz (Journal of Postgraduate Medical Institute, 2015)
Scabies is commonly characterized by the presence of itchy rash but this typ-ical symptom does not necessarily always mean scabies. A female infant pre -sented to the paediatrics department of Kuwait teaching hospital with a char -acteristic pruritic rash on soles suggestive of scabies. However, failure of the anti-scabies treatment, absence of positive personal and hygienic history and progression towards the deterioration of existing situation lead to the estab-lishment of a history and clinical based diagnosis of Infantile Acropustulosis. The treatment was started accordingly and soon after starting treatment, the patient showed the signs of recovery. No doubt that scabies is comparatively more common as compared to infantile acropustulosis but yet scabies must not be considered as an absolute diagnosis for a patient presenting with an itchy rash particularly on soles.